Fundusperimetrie in der Glaukomdiagnostik - Rohrschneider, Klaus; Issa, P. C.; Springer, C.; Scheuerle, Alexander F. (Der Ophthalmologe, 2012)
Examination of the visual field using static automated perimetry (SAP) is the method of choice for the detection of functional damage secondary to glaucoma. However, with SAP early visual field defects might be missed even if there is already visible damage of the retinal nerve fibre. The microperimetry or beter fundus perimetry provides a detailed examination of the differential luminance threshold within defined retinal areas. However, in contrast to lesions of the retinal receptors, in cases of glaucomatous damage the retinal fibre course has to be considered resulting in a displacement between the structural lesion and the location of the related functional defect. The functional damage may be detected at earlier stages and with enhanced spatial resolution compared to conventional SAP. The extra costs and time associated with the application of fundus perimetry have prevented its widespread use. Current developments are leading to new options.
Gesehen am 09.04.2018